Experimental study and calculation of confinement relationships for prestressed steel tube-confined compressed concrete stub columns - Nematzadeh, Mahdi; Naghipour, Morteza; Jalali, Javad; Salari, Abolghasem (Journal of Civil Engineering and Management, 2017)
The current paper aims to present the results of an experimental investigation into the compressive strength of pre-stressed steel tube-confined compressed concrete (PSTC) stub columns. Here, to prestress the confined concrete, an innovative technique is utilized, in which the fresh concrete is subjected to compression while the steel tube is simultaneously preten-sioned laterally by applying external pressure to the fresh concrete. A total of 135 confined specimens were tested under axial compressive loading to determine the confinement strength of the specimens. Moreover, new confinement relationships for the load-carrying capacity of the PSTC columns were proposed in terms of the prestressing ratio (Pr), reference concrete strength (fc), and tube outer diameter to wall thickness ratio (D / t). Finally, a parametric study was conducted to evaluate the effect that the parameters Pr, fc, and / Dt have on the compressive strength of the prestressed confined concrete. The results indi-cate that the confined concrete prestressed by the present technique demonstrates significantly enhanced load-carrying capacity; however, increasing the prestressing level slightly affects it.